PERSONAL, SOCIAL, AND ENVIRONMENTAL FACTORS INFLUENCING SEDENTARY BEHAVIOR IN LONG-TERM CARE COMMUNITY RESIDENTS. (11th November 2018) - Kotlarczyk, M; Hergenroeder, A; Gibbs, B; Cameron, F; Hamm, M; Brach, J
Abstract: Sedentary behavior, sitting with low energy expenditure during waking hours, has emerged as an important public health issue in the past decade. More time spent being sedentary is associated with increased mortality risk, independent of time spent doing moderate-to-vigorous intensity physical activities. Interventions to reduce sedentary behavior have largely focused on children and working adults even though older adults represent the most sedentary age group. Determining modifiable influences on sedentary behavior is essential for designing effective interventions in this overlooked population. We conducted eight focus groups across two independent living and two assisted living communities to explore the personal attitudes, social influences, and environmental factors that affect the sedentary behavior of long-term care community (LTCC) residents. Audio-recordings were transcribed and coded for salient themes using an iterative approach. Participants discussed concerns about their physical abilities, with difficulty standing and fear of falling contributing to more sedentary behavior. Many participants also felt that low activity levels are an inevitable part of aging. The importance of personal motivation to seek out and participate in activities was also discussed. Influences of the social and physical LTCC environment were raised including social activities and meals that require residents to be seated for bouts of an hour or more. Several participants felt facility amenities and services led to a more sedentary lifestyle. Our results indicate that interventions to reduce sedentary behavior in LTCCs should consider not only individual behavior change strategies, but also incorporate approaches to address the unique influences of the LTCC living environment.